2020
DOI: 10.1038/s41598-020-77991-2
|View full text |Cite
|
Sign up to set email alerts
|

Genotype selection for phytochemical content and pharmacological activities in ethanol extracts of fifteen types of Orthosiphon aristatus (Blume) Miq. leaves using chemometric analysis

Abstract: Orthosiphon aristatus (Blume) Miq. of the Lamiaceae family, called as kumis kucing in Indonesia, is a valuable medicinal plant for their pharmacological properties. The present study comprised of fifteen genotypes of O. aristatus was undertaken to evaluate the genotypes based on phytochemical content and pharmacological activities of leaves ethanol extract. Chemometric analysis (correlation and principal component analysis) was also used to investigate the genetic variability based on phytochemical content and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 47 publications
2
26
3
1
Order By: Relevance
“…The purple variety has a purple crown color, while the white-purple variety is white-purple. These results were in line with the studies reported Batubara et al, 2020;Faramayuda et al, 2020).…”
Section: Morphological Identification and Characterizationsupporting
confidence: 93%
“…The purple variety has a purple crown color, while the white-purple variety is white-purple. These results were in line with the studies reported Batubara et al, 2020;Faramayuda et al, 2020).…”
Section: Morphological Identification and Characterizationsupporting
confidence: 93%
“…The FRAP of the individual extracts was determined using a previously documented method. 25 Here, 100 l of extract was briefly added to the 300 l FRAP reagent in the 96-well microplate (Costar-USA). The FRAP reagent was prepared by mixing 300 mM of pH 3.6 acetate buffer with TPTZ (10 mM, in 40 mmol HCl) and 20 mmol FeCl3 with v/v/v ratio of 10:1:1 and incubated for thirty (30) minutes at 37C.…”
Section: Determination Of the Ferric Reducing Antioxidant Power (Frap)mentioning
confidence: 99%
“…Faktor yang berpengaruh pada kadar sinensetin dalam tanaman kumis kucing adalah usia, tingkat kematangan dan lokasi tumbuh. Berdasarkan usia dan tingkat kematangan yang sama, kadar sinensetin beberapa genotype kumis kucing varietas putih lebih tinggi dibandingkan varietas lainnya (Batubara et al, 2020). Penelitian identifikasi dan isolasi senyawa marker sinensetin pada tanaman kumis kucing varietas putih belum banyak dilaporkan.…”
Section: Pendahuluanunclassified